Control of inverted pendulum-cart system based on fuzzy logic approach - Hashim, Hasrulnizam (2013)
This project involves the design of software simulation to make the inverted pendulum to remain upright. The pendulum will depend on the cart so that it can oscillate in a clockwise and counter clockwise direction. Next the cart will be able to move along a straight line along the direction in which the pendulum swings. With the dynamic that drive the cart’s motor along the track as the motion of the pendulum, the pendulum is actually will be prevented from falling from an upright position. Inverted pendulum control problem in this way is a classic way for the control system, because the system is inherently unstable. The pendulum will not remain upright without external force. This type of system is also very difficult to control manually, and thus it is requires the use of electronic controls. In this project, the control algorithms used are the fuzzy logic and PID which is an AI controller and classical controller respectively. Both algorithms will be implemented digitally using MATLAB Simulink software. Finally, this project will demonstrate the effectiveness of control system to stabilize the inverted pendulum quickly, and it will also show the stability control system to unexpected interruptions or disturbances.